Reduction of free fatty acid (FFA) from crude palm oil by using high amplitude sonic wave: article - Ahmad Fauzi, Zafirah; Ku Hamid, Ku Halim (2019)
The amount of free fatty acid (FFA) in crude palm oil (CPO) is a parameter to determine a good quality in palm oil production. FFA is present as a consequence of cell damage in vegetable tissue during each process from harvesting until it can be processed into oil. Producing a high-quality CPO with lower than 5% of FFA required high cost, longer time treatment and at high temperature. Using the treatment from the ultrasonic can increase the quality of palm oil from the cavitation of the bubbles produced which creates the compression and decompression of energy. Comparison of various method of a magnetic stirrer, aerator and ultrasonic by using different parameters of solvent, temperature and time are studies. The results of using ultrasonic with the ratio of oil to solvent at 1:1.8 for ethanol and hexane solvent at the temperature of 45oC in 60 minutes give a significant result to reduce the FFA in low percentage. The removal of FFA and yield extraction from this study are 43.74% and 45.61%. The study concludes that the ultrasonic method can be applied as an alternative method for pre-treatment of CPO which reduces FFA below 5%.